Moralitas Seorang Pemimpin dalam Bernegara Prespektif Etika Politik Islam - Ali Zaenal Abidin Hasan; Husairi Husairi; Kurniati Kurniati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Political ethics in Islam has a very important role in the state, especially in upholding the morality of a leader. The difference in morals, and ethics lies in the foundation used to judge good and bad. Therefore, the principles of Islamic political ethics that a leader should adhere to include mutual respect, recognising the rights of others, accepting various views, and avoiding the suppression of one's own will. The actualisation of morals includes how a person applies their faith and applies Islamic teachings in every daily action, both in relationships with God, self, and fellow humans. This research uses a qualitative approach with the Islamic law literature review method. This method involves searching and analysing references from books and journals that discuss the Morality of Leaders in the State from the Perspective of Islamic Political Ethics. A leader must not only have good morality, but also be intelligent, competent in his field, and wise in solving problems, to create an ideal leader with good morality.